The Influence of the Use of Audio-Visual Media on Student Learning Outcomes on Biodiversity Material at State Senior High School 1 Sukodadi - Norma, Getrina Putri; Faizin, Nur; Amal, Galih Ikhlasul; Rohana Sufia; Nuriza Dora (International Journal of Geography, Social, and Multicultural Education, 2025)
The aim of this study is to determine the influence of using Audio-Visual Media on Students' Learning Outcomes in the subject of Biodiversity at SMA N 1 Sukodadi. This research employs a Quasi-Experimental method with a Nonequivalent Control Group Design. The population of this study consists of four classes of eleventh-grade students in Phase F. The sample includes students from class XI C.2 as the control group, receiving conventional treatment, and students from class XI C.3 as the experimental group, receiving audio-visual media treatment. Data collection was carried out through pretests and posttests on students' learning outcomes, complemented by observations and documentation. Data analysis was conducted using parametric statistics with a T-Test. The results of this study indicate that the use of audio-visual media in the experimental class has a significant effect on improving students' learning outcomes in the subject of biodiversity. The average increase in students' learning outcomes (pretest and posttest) in the experimental class is higher than in the control class, with a comparison of 76.2% and 30.58